2022
DOI: 10.5812/semj-122982
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oral Cinnamon Capsule on the Treatment and Recurrence of Candidal Vaginitis: A Double-blind Randomized Clinical Trial

Abstract: Background: Vaginitis is one of the most common complaints in women around the world. Cinnamon is one of the medicinal plants for which there is contradictory evidence of its effect on vaginitis. Objectives: This study aimed to evaluate the effect of cinnamon on the treatment and recurrence of candidal vaginitis. Methods: We performed this randomized, double-blind, placebo-controlled trial from April to August 2014 in Tehran, Iran. Totally 120 women aged 15 to 45 years clinically and paraclinical approved cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…2,4,6 Almost all women have experienced it at least one time during their lifetime, making this condition a common complaint of women worldwide and this gynecological diagnosis frequently found in the primary health services. [6][7][8] Vaginal infections can cause high stress, dissatisfaction with life, depression, low self-esteem, and decreased sexual activity as well as infertility. 9 Other studies have found that vaginitis causes anxiety, embarrassment, and related concerns about hygiene, especially problems regarding recurring symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…2,4,6 Almost all women have experienced it at least one time during their lifetime, making this condition a common complaint of women worldwide and this gynecological diagnosis frequently found in the primary health services. [6][7][8] Vaginal infections can cause high stress, dissatisfaction with life, depression, low self-esteem, and decreased sexual activity as well as infertility. 9 Other studies have found that vaginitis causes anxiety, embarrassment, and related concerns about hygiene, especially problems regarding recurring symptoms.…”
Section: Introductionmentioning
confidence: 99%